Cross sections for (n, 2n), (n, p), (n, a) and (n, n′) reactions on hafnium isotopes around the neutron energy of 14 MeV - Yong Li; Fengqun Zhou; Yueli Song; Xinyi Chang; Pengfei Ji; Xiaojun Sun; Guoqiang Li (New Journal of Physics, 2020)
In view of the fact that the fast-neutron experimental cross-section data of hafnium which is an important structural material of fusion reactor are few and there are the great differences in their evaluation values, several activation cross sections of (n, 2n), (n, p), (n, a) and (n, n′) reactions on hafnium isotopes have been investigated by neutrons generated from the T(d, n) ^4 He reaction at the K-400 Neutron Generator at China Academy of Engineering Physics (CAEP). The gamma activities of the product nuclei were measured by a high-resolution gamma-ray spectrometer with a coaxial high-purity germanium detector. The ^93 Nb(n, 2n) ^92m Nb reaction was used as neutron fluence standard, these experimental cross sections of the ^174 Hf(n, 2n) ^173 Hf, ^176 Hf(n, 2n) ^175 Hf, ^178 Hf(n, α ) ^175m+g Yb, ^178 Hf(n, p) ^178g Lu, ^178 Hf(n, p) ^178m Lu, ^180 Hf(n, 2n) ^179m2 Hf, ^180 Hf(n, α ) ^177m+g Yb and ^180 Hf(n, n′) ^180m Hf reactions were obtained in the neutron energy range of 13.5–14.8 MeV. These measured cross sections were discussed and compared with some previous experimental results from the literature and with the evaluation data from ENDF/B-VIII.0, CENDL-3.1, JEFF-3.3 and the theoretical results by using the computer code system Talys-1.9.